Comparative analysis of regional development: Exploratory space-time data analysis and open source implementation - Xinyue Ye; Wenze Yue (Kiel Institute for the World Economy (IfW), 2014)
This paper aims to make contributions to comparative analysis of regional economic dynamics in China and the US from the methodological perspective. More specifically, some recent advances in exploratory space-time data analysis (ESTDA) will be suggested and implemented to conduct this task in an open source environment. China and the US have been the subject of much discussion about the patterns and trends of regional development, because of their importance in the world economic system. Despite the rich and growing empirical literature on numerous case studies at both national and sub-national scales, comparative space time analysis between and within these two economic systems has just begun to catch attentions. Additionally, ESTDA and its open source implementation can facilitate comparative studies of regional development.
Keywords: C21; C88; 330; ETSDA; regional development; comparative analysis; open source; China; USA